Cognitive and Academic Outcomes Following Childhood Cortical Stroke. (December 2019) - Peterson, Rachel K.; Williams, Tricia S.; McDonald, Kyla P.; Dlamini, Nomazulu; Westmacott, Robyn
The majority of pediatric neuropsychological stroke research has focused on perinatal stroke outcomes given its relative frequency. Meanwhile, childhood-onset stroke is under-represented in the literature, resulting in limited knowledge about its neurocognitive sequelae. This retrospective study examined cognitive outcomes in children and youth (n = 27) with childhood arterial ischemic stroke (stroke occurring between 29 days and 18 years of life) isolated to the cortical region. Intellectual, academic, language, visual-perception, visual-motor integration, fine motor coordination, and executive function scores were examined relative to normative means. Results indicate that although these children are doing well in terms of general intellectual ability, they demonstrate lower scores on tasks of processing speed and fine motor coordination. Exploratory analysis also revealed that of the personal and neurologic factors examined, age at stroke was positively correlated with perceptual reasoning and fine motor control, age at assessment was negatively correlated with math calculation abilities, and maternal education was positively correlated with working memory and parent-reported behavioral regulation and impulse inhibition abilities. While neurologic variables were not predictive of cognitive neuropsychological outcomes, those with significant poorer performance had higher rates of medium/large, right-sided lesions with frontal lobe involvement. Our results highlight the overall resilience of the injured developing brain but also the vulnerability of specific cognitive skills within this unique population.